Yield-per-Recruit and Relative Mean Biomass Estimates, and their Management Consequences, to the Penaeus Indicus Fishery in the Gulf of Masirah - M. S. M. Siddeek; R. Mohan; D. W. Johnson (Journal of Agricultural and Marine Sciences, 1996)
The von Bertalanffy growth parameters estimated based on the 1990/91 carapace length data of Penaeus indicus  from the Gulf of Masirah, Oman were used to calculate total mortality, yield-per-recruit ( i.e. average weight of a shrimp from a cohort under a given fishing pattern) , and relative mean biomass ( i.e. exploited cohort biomass over un-exploited cohort biomass) for the population sampled. The instantaneous total mortality coefficient value indicated under exploitation in 1990/91. When different fishing seasons scenarios were considered with the current total mortality level but with a range of natural mortality values, high yield, per recruit and relative mean biomass values were shown for October-April and November-April fishing seasons. The fishing season is currently late August to end of April. Thus, a one to two-month delay in the fishing season appears to be beneficial to this fishery.